ANALISA SISTEM PEMBANGKIT BERBASIS THERMOELEKTRIK DENGAN RANGKAIAN SERI PADA PEMANFAATAN PANAS BUANG MESIN TOYOTA TIPE 4K - Ahmad Farid; Lagiyono .; Yanu ivayana (Engineering : Jurnal Bidang Teknik, 2011)
Thermoelectric technology is themain alternative source for ansver theneed of energy. Thermoelectric can produce hot or cool. The sape is slim, size 4 x 4 cm and thickness just 4 mm. This research aim to detected the use of heat sink Toyota machine type 4K with thermoelectric modul and the application from energy that is producted by series of thermoelectric modul. Method that is used in this research is method research, the object of this research thermoelectric modul that is used for using heat sink in machine and continued by the application economizing on fuel. Based on the result of research from 8 thermoelectric modul series produced electric tension (voltase) 6,6 Volt with 1 Ampere electric current but after applicated for electrolysis, tension become 2,5 Volt with electric current 0,1. Electric power that is applicated 6,6 watt and after applicate in electrolysis become 0,22 watt. The use application electric energy from thermoelectric with electrolysis method get satisfying result. The use of fuel in 50 minute without electrolysis fuel that need in 50 minute is 910 mililiter. it means in 50 minute using electrolysis we can economize fuel 130 mililiter. Key words: thermoelectric, electrolysis, econo mizing in fuel.